CAUSAL MODEL OF FACTORS INFLUENCING SHOPPING BEHAVIOR OF GENERATION-Y - Tivarat Sriratree; Opal Suwannamek; Chalita Srinuan (My University, 2024)
Purpose: The objective of this research was to study the variables that affect the online shopping behavior of Generation-Y. Methods: This research was conducted using quantitative methods utilizing a questionnaire as the primary tool to collect data from 300 samples of Gen-Y group who use online shopping services. The statistics used in the data analysis comprised descriptive statistics and structural equation model analysis. Results and Discussions: The results showed that the maximum mean factors were online shopping behavior (mean=5.54, SD.= .681), intention to purchase (mean=5.52, SD.= .704), and subjective norms (mean=5.19, SD.=.924), respectively. The results of casual model analysis found that intention to purchase, and subjective norms affected the online shopping behavior of Y Gen consumers with statistical significance. However, the controllability factor was not statistically significant. Research Implications: Therefore, consumers' perceptions of using technology through social media purchases are seemingly increasing. Accordingly, entrepreneurs in the e-market should use big data to analyze consumer behavior, communicate with consumers, and publicize information efficiently. Consumer groups want to try new things and challenges, and like using a convenient internet to save time, searching products, purchase, and make transactions on one platform via social media. Conclusions: The retail industry has fully entered the digital age, which is evident by the vast number of consumers who use various online platforms. Further, this trend is continuously increasing due to the constant development of modern technology to facilitate consumers and increase the efficiency of commerce. At present, changing consumer behaviors affect various activities and consumption behaviors, especially in terms of consumers spending less time purchasing products in stores and spending more time buying goods and services online using various technological means. Also, this fact tends to significantly increase e-commerce. Originality/Value: It could also be used to reach new target customers to provide more convenience or search for new products that could be acquired easily, even if originating from different continents to help facilitate, save time, and create tremendous business opportunities.
Keywords: Entrepreneurship Studies and Influences